Trends in fall-related ambulance use and hospitalisation among older adults in NSW, 2006-2013: a retrospective, population-based study - Serene S Paul; Lara Harvey; Therese Carroll; Qiang Li; Soufiane Boufous; Annabel Priddis; Anne Tiedemann; Lindy Clemson; Stephen R Lord; Sandy Muecke; Jacqueline CT Close; Serigne Lo; et al. (Sax Institute, 2017)
Objective and importance of study: To describe characteristics and temporal trends of fall-related ambulance service use and hospital admission in older adults in New South Wales (NSW), Australia. Such information will facilitate a more targeted approach to planning and delivery of health services to prevent falls and their adverse sequelae in different groups of older adults. Study type: Retrospective population-based descriptive study. Methods: Fall-related ambulance use and hospital admissions for all falls and injurious falls in NSW residents aged ≥65 years between 2006 and 2013 were obtained from two discrete sources of routinely collected data. Rates of use are presented descriptively. Results: There were 314 041 occasions of fall-related ambulance use by older adults and 331 311 fall-related hospitalisations, of which 69% (n = 227 753) were for injurious falls. Fractures accounted for 57% of injurious hospitalisations. Slips and trips were the most common mechanism of falls requiring hospitalisation (52%). Residents of aged care facilities had a greater proportion of fall injury hospitalisations compared with people living in the community (85% and 65%, respectively). Conclusions: Rates of fall-related ambulance use and hospitalisation were similar and continued to increase over time. Increased effort is needed to prevent falls and associated injury among older people in NSW, particularly among people living in aged care facilities. Ongoing monitoring of rates and the characteristics of people who fall are needed to determine the long-term impact of fall prevention interventions.